ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DAN KETERAMPILAN METAKOGNISI SISWA PADA TOPIK GEOMETRI DITINJAU DARI GENDER - Putri Wulansari, - (2022)
Mathematics problem solving ability and metacognition skills are very important to be improved by students. Based on the preliminary study that has been done that there is an inconsistency in the mathematics problem solving ability and students' metacognition skills between male students and female students. So that researchers are interested in investigating and exploring further the mathematics problem solving abilities and metacognitive skills of students in terms of gender. The purpose of this study was to obtain an overview of students' mathematics problem solving abilities and metacognitive skills on the topic of geometry in terms of gender. This research method is an exploratory case study, with research subjects as many as 46 students at one public junior high school in Bandung regency and one public junior high school in Bandung city. Analysis of the data in this study using data analysis Miles and Huberman includes data reduction, data presentation, and drawing conclusions. The results of this study indicate that the majority of students' mathematics problem solving abilities are moderate, but at the Polya mathematics problem solving stage students can fulfill all Polya stages except the looking back stage which has the lowest percentage namely 4.17%. Meanwhile, students' metacognition skills have problems at the planning and evaluating stages. In terms of gender, students' mathematics problem solving abilities are dominated by androgynous and feminine students. Students with this high category almost fulfill all stages of Polya. Meanwhile, students in the medium-low category only fulfilled several stages of Polya. Then, on the metacognitive skills of female students, the feminine gender has the highest percentage, which is 80.95%. Meanwhile, students with other genders have percentages between 59.09% and 69.05%. Furthermore, the relationship between mathematics problem solving abilities and students' metacognitive skills was categorized as moderate (enough). The impact of this study shows that gender factors and categories of students' abilities have an influence on mathematics problem solving abilities and students' metacognitive skills on the topic of geometry. Keywords: Mathematics Problem-Solving Ability, Metacognitive Skills, Topic Geometry, Gender